Tìm đạo hàm của hàm số \(y=\dfrac{\mathrm{e}^x+\mathrm{e}^{-x}}{\mathrm{e}^x-\mathrm{e}^{-x}}\).
\(y'=\dfrac{\mathrm{e}^x}{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)^2}\) | |
\(y'=\dfrac{-4}{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)^2}\) | |
\(y'=\dfrac{-5}{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)^2}\) | |
\(y'=\mathrm{e}^x+\mathrm{e}^{-x}\) |
Chọn phương án B.
Dùng máy tính cầm tay:
Chọn phương án B.
\(\begin{aligned}
y'&=\dfrac{\left(\mathrm{e}^x+\mathrm{e}^{-x}\right)'\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)-\left(\mathrm{e}^x+\mathrm{e}^{-x}\right)\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)'}{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)^2}\\
&=\dfrac{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)-\left(\mathrm{e}^x+\mathrm{e}^{-x}\right)\left(\mathrm{e}^x+\mathrm{e}^{-x}\right)}{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)^2}\\
&=\dfrac{\left(\mathrm{e}^{2x}-2+\mathrm{e}^{-2x}\right)-\left(\mathrm{e}^{2x}+2+\mathrm{e}^{-2x}\right)}{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)^2}\\
&=\dfrac{-4}{\left(\mathrm{e}^x-\mathrm{e}^{-x}\right)^2}.
\end{aligned}\)